Synovial sarcoma mimicking infrapatellar bursitis: A diagnostic challenge - Murat Acar, MD; Angela G. Niehaus, MD; Julian B.H. Acevedo, MD; Scott D. Wuertzer, MD (Radiology Case Reports)
Synovial sarcoma (SS) is an uncommon, aggressive soft tissue tumor that primarily affects young individuals. We present a case of a 17-year-old male with a 4-year history of anterior knee pain, initially suspected to have infrapatellar bursitis based on noncontrast MRI findings. This case highlights imaging characteristics of SS that may mimic benign conditions, leading to diagnostic challenges, particularly on noncontrast MRI.